IMF Survey : Volume 28, Issue 17. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1999)
The rationale for IMF lending to Russia has been widely questioned, as have the record of earlier programs and the use made of previous IMF loans. In the following article, John Odling-Smee, Director of the IMF's European II Department, explains that the resumed lending was fully justified to support Russia's most recent economic policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet